How would you recognise an expert coach if you saw one? - Wharton, L.; Rossi, T.; Nash, C.; Renshaw, I. (International Journal of Sports Science and Coaching, 2015)
Literature that frames coaching practice and specifically the formation and determination of expert coaching practice reveals a body of research that generally lacks continuity. Importantly, arguments relating to the instability of professional interpretations of coaching practice appear to stem from a penchant for subjective investigation. This analysis draws on an extensive review of peer-reviewed articles, chapters and books - all published within the last 35 years that address the notion of coaching practice. The key themes to emerge point to the idea that much of the research used to establish conceptual clarity fails to distinguish between highly organised or efficient coaching practice and expert coaching practice. This paper concludes with some suggestions from alternate paradigms and disciplines that suggest that expertise in interceptive sports coaching may be better theorised and suitably identified through a lens of the growing ideas surrounding the concept of `emergence`.